Spinel oxide catalyst as well as preparation method and application thereof
By adopting a spinel oxide catalyst with a hollow nanotube-like structure, its active components include NiCo2O4, the problem of insufficient specific surface area and active sites of spinel transition metal oxides in the OER catalyst is solved, and high efficiency is achieved OER electrocatalytic activity and good electrochemical properties.
Patent Information
- Application Number
- CN202411792941.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-21
AI Technical Summary
As an OER catalyst, spinel-type transition metal oxides have limited specific surface area, number of active sites and poor conductivity problems, which limit their performance in the process of electrolyzing of oxygen.
By utilizing a spinel oxide catalyst with a hollow nanotube-like structure, its active component includes NiCo2O4, a catalyst with a high specific surface area is obtained by calcining using nanowires covered with carbon as a template.
Achieve high specific surface area of the catalyst, provide more reactive sites, improve OER electrocatalytic activity, and exhibit excellent electrochemical properties, including small charge transfer resistance, good reaction kinetics and cycle stability .
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrolyzing water to produce oxygen, and in particular relates to a spinel oxide catalyst and a preparation method and application thereof. Background Art
[0002] In recent years, in order to meet the growing demand for environmental protection, the development of new energy sources is imminent. Compared with traditional fossil fuels, hydrogen has become an ideal green energy fuel in the future. At present, water electrolysis is a method with great application prospects for producing high-purity hydrogen. The process of water electrolysis includes two half-cell reactions, namely hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). Due to the slow kinetics of four-electron transfer, OER is considered to be the rate-limiting step in the water electrolysis process. Therefore, the development of an efficient and stable OER catalyst is a necessary condition for the practical application of water electrolysis.
[0003] In recent years, spinel transition metal oxides (TMOs) have been intensively studied to replace the expensive traditional OER electrocatalysts such as RuO2 and IrO2 due to their relative abundance, low cost, and low toxicity. By controlling the surface microstructure, regulating the composition of each element, and adjusting the electronic structure by heteroatom doping, efficient OER catalysts can be prepared, mainly including metal oxides and peroxides such as Ni, Co, and Fe.
[0004] However, spinel transition metal oxides still have some shortcomings and challenges when used as OER catalysts, such as limited specific surface area, number of active sites and poor conductivity. The performance of electrocatalytic materials is closely related to the microstructure of the active materials, so it is critical to manufacture clear morphologies with adjustable sizes, macro / mesopores and nanostructures of the materials. Based on the above considerations, it is of great significance to develop NiCo2O4 with new controllable morphologies and structures to improve its electrochemical performance. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a spinel oxide catalyst and a preparation method and application thereof. The catalyst has more reactive sites, so that it has excellent OER electrocatalytic activity.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a spinel oxide catalyst, the active component of which includes NiCo2O4.
[0008] Preferably, the structure of the spinel oxide catalyst is a hollow nanotube structure.
[0009] Preferably, the diameter of the hollow nanotube is 90-120 nm.
[0010] In a second aspect, the present invention provides a method for preparing the above spinel oxide catalyst, comprising the following steps:
[0011] S1: mixing a soluble nickel salt, a soluble cobalt salt, a precipitant and a solvent to obtain a mixed solution;
[0012] S2: mixing and reacting the mixed solution with the template dispersion to obtain a precursor, and calcining to obtain a spinel oxide catalyst;
[0013] The template in the template dispersion is a nanowire with carbon coated on the surface.
[0014] Preferably, the soluble cobalt salt includes but is not limited to cobalt nitrate, cobalt sulfate or cobalt chloride.
[0015] Preferably, the soluble nickel salt includes but is not limited to nickel nitrate, nickel sulfate or nickel chloride.
[0016] Preferably, the precipitating agent includes but is not limited to urea.
[0017] Preferably, the solvent includes but is not limited to water.
[0018] Preferably, the ratio of the soluble cobalt salt, the soluble nickel salt, the precipitant and the solvent is 1 mmol: 0.5 mmol: (7-8) mmol: (5-15) mL
[0019] Preferably, the nanowires are selected from tellurium nanowires.
[0020] Preferably, the mixing in step S2 is performed under stirring conditions; the stirring rate is 10000~14000r / min.
[0021] Preferably, the reaction temperature in step S2 is 130-150° C. and the reaction time is 6-8 h.
[0022] Preferably, the heating rate of the calcination is 2-5°C / min, the calcination temperature is 350-500°C, and the calcination time is 1-3 h.
[0023] Preferably, after the precursor is obtained in step S2, it is washed and dried, and then calcined;
[0024] Preferably, the washing is performed by washing with ethanol and water for 3 to 5 times respectively.
[0025] Preferably, the drying temperature is 60-70° C. and the drying time is 12-18 h.
[0026] In a third aspect, the present invention provides a use of the spinel oxide catalyst in oxygen evolution by electrolysis of water.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The present invention provides a spinel oxide catalyst, the active component of which includes NiCo2O4. In the present invention, the structure of the spinel oxide catalyst is a hollow nanotube structure, which is composed of NiCo2O4 particles. With the help of the hollow nanotube structure, the specific surface area of the catalyst is large, thus providing more reactive active sites, and also facilitating the diffusion of electrolyte and the desorption of gas in the process of electrolyzing water and oxygen evolution.
[0029] The spinel oxide catalyst has a current density of 50 mA / cm in the OER performance test. 2 The overpotential at 420 mV is much higher than the OER catalytic performance of commercial RuO2 (50 mA / cm 2 The overpotential at 488 mV shows that it has excellent OER electrocatalytic activity. At the same time, the catalyst also has a small charge transfer resistance, good reaction kinetics and cycle stability.
[0030] In addition, the preparation method of the catalyst has the advantages of simple operation, low cost, high repeatability, and is easy to realize large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 X-ray diffraction patterns of the tubular structured spinel oxide catalysts prepared in Example 1, Example 2 and Example 3;
[0032] Figure 2 This is a scanning electron microscope image of the tubular structure spinel oxide catalyst prepared in Example 1;
[0033] Figure 3 A transmission electron microscopy image of the tubular structured spinel oxide catalyst prepared in Example 1;
[0034] Figure 4 (a) is a wide range XPS spectrum of the tubular spinel oxide catalyst prepared in Example 1;
[0035] Figure 4 (b) is a detailed XPS spectrum of Ni 2p of the tubular structured spinel oxide catalyst prepared in Example 1;
[0036] Figure 4 (c) is a detailed XPS spectrum of Co 2p of the tubular structured spinel oxide catalyst prepared in Example 1;
[0037] Figure 4 (d) is the detailed XPS spectrum of O 1s of the tubular spinel oxide catalyst prepared in Example 1;
[0038] Figure 5 Polarization curves of the tubular spinel oxide catalyst prepared in Example 1, the tubular ZnCo2O4 prepared in Comparative Example 1, the tubular CoFe2O4 prepared in Comparative Example 2 and commercial RuO2 in 1 M KOH at a scan rate of 5 mV / s;
[0039] Figure 6 The Tafel curve of the spinel oxide catalyst with a tubular structure prepared in Example 1;
[0040] Figure 7 This is a cyclic stability test of the tubular spinel oxide catalyst prepared in Example 1, and a polarization curve diagram before and after 1000 CV cycles;
[0041] Figure 8 OER cyclic voltammetry curves (CV) of the tubular spinel oxide catalyst prepared in Example 1 at different scan rates within the non-Faraday current region;
[0042] Fig. 9 The double layer capacitance (C) obtained by measuring the capacitance and current response of the tubular spinel oxide catalyst prepared in Example 1 at different scan rates using CV dl );
[0043] Fig.10 This is the impedance spectrum (EIS) of the tubular structure spinel oxide prepared in Example 1 at 1.623 V vs. RHE. DETAILED DESCRIPTION
[0044] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] The present invention provides a spinel oxide catalyst, the active component of which includes NiCo2O4 (reference Figure 1 ).
[0046] In the present invention, the NiCo2O4 exists in the form of nanoparticles and eventually forms a spinel oxide catalyst having a hollow nanotube structure (such as Figure 2 and Figure 3 ), thereby providing more reactive sites.
[0047] In the present invention, the diameter of the hollow nanotube is 90-120 nm.
[0048] The present invention also provides a method for preparing the spinel oxide catalyst having a hollow nanotube structure, comprising the following steps:
[0049] S1: mixing a soluble nickel salt, a soluble cobalt salt, a precipitant and a solvent to obtain a mixed solution;
[0050] S2: mixing the mixed solution with the template dispersion and reacting them to obtain a precursor, and calcining them to obtain a spinel oxide catalyst.
[0051] First, a soluble nickel salt, a soluble cobalt salt, a precipitant and a solvent are mixed to obtain a mixed solution. In the present invention, the soluble cobalt salt includes but is not limited to cobalt nitrate, cobalt sulfate or cobalt chloride; the soluble nickel salt includes but is not limited to nickel nitrate, nickel sulfate or nickel chloride; the precipitant includes but is not limited to urea; the solvent includes but is not limited to water, preferably water, and more preferably deionized water.
[0052] In some embodiments of the present invention, the soluble cobalt salt, the soluble nickel salt, the precipitant and the solvent are preferably mixed in a ratio of 1 mmol: 0.5 mmol: (7-8) mmol: (5-15) mL, preferably 1 mmol: 0.5 mmol: (7.5-8) mmol: (10-15) mL to obtain a mixed solution. More preferably, the soluble nickel salt, the soluble cobalt salt and the precipitant are dissolved in a solvent and dispersed by ultrasound.
[0053] In the present invention, the template in the template dispersion is a nanowire with carbon coated on the surface. The nanowire, as a template, provides a one-dimensional confined space, so that the final product (i.e., the catalyst precursor) can only expand in this dimension, thereby forming a one-dimensional structure with a specific shape and size; unlike the spherical template, after the nanowire template is removed, the two ends of the product are open, and the inner wall can also communicate with the outside world, which helps to improve the electrocatalytic performance. In addition, the nanowire template can improve the agglomeration of NiCo2O4 particles subsequently deposited on its surface to a certain extent.
[0054] In some embodiments of the present invention, the nanowires are selected from tellurium (Te) nanowires.
[0055] In the present invention, the tellurium nanowires can be prepared according to the method provided by the prior art.
[0056] Exemplarily, in some embodiments of the present invention, the preparation of the Te nanowires comprises the following steps:
[0057] Dissolve polyvinyl pyrrolidone and Na2TeO3 in deionized water, stir magnetically, and add hydrazine hydrate and concentrated ammonia water to the solution. Transfer the final solution to a polytetrafluoroethylene hydrothermal reactor, place it in an oven at 180°C for 3 h, and obtain a Te nanowire solution. After the sample is naturally cooled to room temperature, add acetone to precipitate the product, centrifuge, and collect the product. The above temperature and time can be reasonably adjusted, and the present invention does not make special restrictions.
[0058] Among them, the above-mentioned polyvinyl pyrrolidone plays the role of a structure directing agent to control the growth of Te nanowires; Na2TeO3, as a tellurium source, can replace other tellurium sources; acetone, as a precipitant when washing samples, can be replaced by other polar organic solvents.
[0059] In the present invention, in the above embodiment, the volume ratio of hydrazine hydrate to concentrated aqueous ammonia used is preferably 1:(1~3), more preferably 1:2; the concentration of concentrated aqueous ammonia is preferably 25~28 wt%, more preferably 26 wt%; the volume ratio of the precipitant acetone to the Te nanowire solution used is (15~20) mL:5 mL, preferably (17~18) mL:5 mL.
[0060] In the present invention, the surface of the nanowire is preferably coated with carbon, which can increase the radial length of the nanowire and improve the specific surface area of the final product.
[0061] In some embodiments of the present invention, taking Te nanowire as an example, the method of coating carbon on the surface of the Te nanowire comprises the following steps:
[0062] 4-6 mL of Te nanowire solution (Te nanowire concentration is 0.010-0.011 mmol / mL) is dispersed into 30-40 mL of glucose solution, stirred magnetically, and then transferred to a polytetrafluoroethylene hydrothermal reactor, placed in an oven at 180°C for 8 h, and the sample is cooled naturally to room temperature. The above temperature and time can be reasonably adjusted and are not specifically limited in the present invention.
[0063] Wherein, the glucose solution as a carbon source can be replaced by other carbon sources, such as chitosan, etc. In the present invention, the mass concentration of the glucose solution is 0.0375-0.0625 g / mL, preferably 0.05 g / mL.
[0064] According to the above content, after obtaining the nanowires with carbon coated on the surface, the mixed solution is mixed with the template dispersion liquid and reacted to obtain a precursor.
[0065] In some embodiments of the present invention, the prepared mixed solution is preferably added dropwise to the template dispersion under vigorous stirring, and then the reaction is maintained at 130-150°C for 6-8 hours, preferably at 140°C for 6 hours. In this process, carbonate ions (CO3 2- ) and hydroxide ions (OH - ) reacts with metal ions to form a basic carbonate precursor, which combines with the functional groups on the template surface (preferably Te@C surface) and is fixed on the template surface to form a shell layer.
[0066] Wherein, the stirring rate is 10000~14000 r / min, preferably 11000~12000 r / min.
[0067] In some preferred embodiments of the present invention, after the above reaction is completed, the sample is cooled naturally to room temperature, centrifuged, washed and dried to finally obtain a powdered sample (ie, a precursor).
[0068] The present invention has no special limitation on centrifugation, washing and drying, and they can be carried out according to means well known to those skilled in the art. In the present invention, the washing is preferably carried out 3 to 5 times with ethanol and water respectively, and the water is preferably deionized water; the drying temperature is 60 to 70°C, preferably 65 to 68°C; and the drying time is 12 to 18 hours, preferably 13 to 15 hours.
[0069] Finally, according to the present invention, the precursor is calcined to obtain a spinel oxide catalyst. During the calcination process, the basic carbonate deposited on the surface of the carbon-coated nanowires will generate NiCo2O4 particles, and the carbon and nanowires will volatilize during the calcination process, and the NiCo2O4 particles will stack on each other, thereby finally forming a spinel oxide catalyst with a hollow nanotube structure.
[0070] In the present invention, the calcination is preferably carried out in an air atmosphere, the calcination temperature is 350-500° C., preferably 350-400° C., and the calcination time is 1-3 h, preferably 1.5-2.5 h.
[0071] In the above calcination process, a too high heating rate will cause the nanotubes to break, and a too low heating rate will cause incomplete volatilization of carbon and nanowires. Therefore, the present invention screens and controls the calcination heating rate to 2-5 °C / min, preferably 3-4 °C / min.
[0072] In summary, illustratively, in some specific embodiments of the present invention, the method for preparing the spinel oxide catalyst is carried out according to the following steps:
[0073] (1) Preparation of Te nanowires: Dissolve polyvinyl pyrrolidone and Na2TeO3 in deionized water, stir magnetically, and add hydrazine hydrate and concentrated ammonia to the solution. Transfer the final solution to a polytetrafluoroethylene hydrothermal reactor and place it in an oven at 180°C for 3 h. Allow the sample to cool naturally to room temperature, add acetone to precipitate the product, centrifuge, and collect the product;
[0074] (2) Preparation of Te / C template:
[0075] The Te nanowires prepared in step (1) were dispersed in a glucose solution, stirred magnetically, and then transferred to a polytetrafluoroethylene hydrothermal reactor and placed in an oven at 180 °C for 8 h, and the sample was allowed to cool naturally to room temperature;
[0076] (3) Preparation of precursor:
[0077] Dissolve soluble nickel salt, soluble cobalt salt and urea in deionized water and disperse by ultrasonic. Add the prepared solution dropwise to the Te / C dispersion obtained in step (2) under vigorous stirring. Place in an oven at 140 °C for 6 h. After the sample is naturally cooled to room temperature, centrifuge, wash and dry it to obtain a powdered sample.
[0078] (4) Preparation of tubular NiCo2O4:
[0079] The precursor powder obtained in step (3) is calcined and oxidized in air to obtain the spinel oxide catalyst.
[0080] It can be seen that the preparation method of the catalyst is simple to operate, low in cost, high in repeatability, and easy to realize large-scale production.
[0081] Based on this, the present invention also provides an application of the spinel oxide catalyst in the electrolysis of water for oxygen evolution. Specifically, the spinel oxide catalyst can be used as a high-efficiency oxygen evolution reaction catalyst in the electrolysis of water for oxygen evolution.
[0082] According to research, the spinel oxide catalyst obtained under a specific technical solution of the present invention has a current density of 50 mA / cm in the OER performance test. 2 The overpotential at 420 mV is much higher than the OER catalytic performance of commercial RuO2 (50 mA / cm 2 The overpotential at 488 mV shows that it has excellent OER electrocatalytic activity. At the same time, the catalyst also has a small charge transfer resistance, good reaction kinetics and cycle stability.
[0083] In order to further illustrate the present invention, the following examples are provided for detailed description. The experimental raw materials used in the following examples of the present invention are all common commercially available products.
[0084] Example 1
[0085] (1) Preparation of Te nanowires: Dissolve 1.2 g polyvinyl pyrrolidone (PVP) and 0.5 mmol Na2TeO3 in 44 mL deionized water and stir. Add 2 mL hydrazine hydrate and 4 mL concentrated ammonia (mass fraction 26 wt%) to the solution. Transfer the final solution to a 100 mL polytetrafluoroethylene hydrothermal reactor and place it in an oven at 180 °C for 3 h. After the sample is cooled to room temperature naturally, add acetone to precipitate the product, centrifuge, and collect the product;
[0086] (2) Preparation of Te / C template: 5 mL of Te nanowires prepared in step (1) were dispersed in 35 mL of glucose solution, stirred, and then transferred to a 100 mL polytetrafluoroethylene hydrothermal reactor and placed in an oven at 180 °C for 8 h. The sample was allowed to cool naturally to room temperature.
[0087] (3) Preparation of precursor: Dissolve 0.5 mmolNi(NO3)2▪6H2O, 1 mmolCo(NO3)2▪6H2O, and 8 mmol urea in deionized water and disperse by ultrasonic. Add the prepared solution dropwise to the Te / C dispersion obtained in step (2) under vigorous stirring. Place in an oven at 140 °C for 6 h. After the sample is naturally cooled to room temperature, centrifuge, wash, and dry it to obtain a powdered sample.
[0088] (4) Preparation of tubular NiCo2O4: The powder obtained in step (3) was ground, placed in a porcelain boat, and heated to 350°C at a heating rate of 3°C / min in an air atmosphere. The temperature was kept at this temperature for 3 h, and the template was removed to obtain a tubular structure spinel oxide high-efficiency oxygen evolution reaction catalyst.
[0089] The tubular spinel oxide prepared in Example 1 is composed of NiCo2O4 ( Figure 1 ). Combined Figure 2 and Figure 3 The prepared tubular spinel oxide has an obvious hollow tubular structure with a diameter of about 90~120 nm, and the tubular structure is composed of nanoparticles, which is beneficial to increase the specific surface area.
[0090] The Ni element in the prepared tubular spinel oxide is Ni 2+ and Ni 3+ The Co element exists in the form of Co 2+ and Co 3+ exists in the form of Figure 4Among the XPS peaks of O 1s, there are three characteristic peaks located at 529.1 eV, 530.5 eV, and 532.6 eV, corresponding to typical metal-oxygen bonds, oxygen vacancies, and hydroxyl groups, respectively.
[0091] Weigh 5 mg of the catalyst powder to be tested into a sample tube, add 970 μL of anhydrous ethanol as a solvent and 30 μL of Nafion solution as a binder, mix them and ultrasonically homogenize them to obtain a black catalyst slurry. Transfer 50 μL of the slurry and drip it on a carbon paper with an area of 0.5 cm×0.5 cm several times to ensure that the slurry is evenly coated on the surface of the carbon paper. Dry it at room temperature overnight and set aside. The carbon paper has been treated with ethanol and acetone in advance. The catalyst loading is 1 mg / cm 2 The carbon paper was used as the working electrode, the carbon rod was used as the counter electrode, and the Ag / AgCl electrode was used as the reference electrode to assemble a three-electrode test system. The OER electrochemical performance test was carried out on an electrochemical workstation (CHI 760E). The OER performance test results of the prepared tubular spinel oxide are shown in Figure 5 As shown, at a current density of 50 mA / cm 2 The overpotential at 420 mV is much higher than the OER catalytic performance of commercial RuO2 (50 mA / cm 2 The overpotential η at the site is 488 mV). Where, overpotential η = E (vs. RHE) - E eq =E (vs. RHE) -1.23 V.
[0092] The prepared tubular spinel oxide has good reaction kinetics, and its Tafel slope is 103.84 mV·dec -1 ,like Figure 6 shown.
[0093] like Figure 7 As shown, the tubular structure spinel oxide prepared by the present invention has good cycle stability. After 1000 cycles, the overpotential of the material does not change much.
[0094] Electrochemically active surface area (ECSA) and electric double layer capacitance (C dl ) have a positive proportional relationship. Figure 8 and Fig. 9 The prepared tubular spinel oxide has a large electrochemically active surface area (C dl 44.43 mF·cm -2 ).
[0095] The prepared tubular spinel oxide has a small charge transfer resistance of 4.781 Ω. Fig.10 .
[0096] Example 2
[0097] (1) Preparation of Te nanowires: Dissolve 1.2 g polyvinyl pyrrolidone (PVP) and 0.5 mmol Na2TeO3 in 44 mL deionized water and stir. Add 2 mL hydrazine hydrate and 4 mL concentrated ammonia (mass fraction 26 wt%) to the solution. Transfer the final solution to a 100 mL polytetrafluoroethylene hydrothermal reactor and place it in an oven at 180 °C for 3 h. After the sample is cooled to room temperature naturally, add acetone to precipitate the product, centrifuge, and collect the product;
[0098] (2) Preparation of Te / C template: 5 mL of Te nanowires prepared in step (1) were dispersed in 35 mL of glucose solution, stirred, and then transferred to a 100 mL polytetrafluoroethylene hydrothermal reactor and placed in an oven at 180 °C for 8 h. The sample was allowed to cool naturally to room temperature.
[0099] (3) Preparation of precursor: Dissolve 0.5 mmol Ni(NO3)2▪6H2O, 1 mmol Co(NO3)2▪6H2O, and 8 mmol urea in deionized water and disperse by ultrasonic. Add the prepared solution dropwise to the Te / C dispersion obtained in step (2) under vigorous stirring. Place in an oven at 140 °C for 6 h. After the sample is naturally cooled to room temperature, centrifuge, wash, and dry it to obtain a powdered sample.
[0100] (4) Preparation of tubular NiCo2O4: The powder obtained in step (3) was ground, placed in a porcelain boat, and heated to 400°C at a heating rate of 3°C / min in an air atmosphere, kept at this temperature for 2 h, and the template was removed to obtain a tubular structure spinel oxide high-efficiency oxygen evolution reaction catalyst.
[0101] The tubular spinel oxide prepared in Example 2 is composed of NiCo2O4 ( Figure 1 ).
[0102] Example 3
[0103] (1) Preparation of Te nanowires: Dissolve 1.2 g polyvinyl pyrrolidone (PVP) and 0.5 mmol Na2TeO3 in 44 mL deionized water and stir. Add 2 mL hydrazine hydrate and 4 mL concentrated ammonia (mass fraction 26 wt%) to the solution. Transfer the final solution to a 100 mL polytetrafluoroethylene hydrothermal reactor and place it in an oven at 180 °C for 3 h. After the sample is cooled to room temperature naturally, add acetone to precipitate the product, centrifuge, and collect the product;
[0104] (2) Preparation of Te / C template: 5 mL of Te nanowires prepared in step (1) were dispersed in 35 mL of glucose solution, stirred, and then transferred to a 100 mL polytetrafluoroethylene hydrothermal reactor and placed in an oven at 180 °C for 8 h. The sample was allowed to cool naturally to room temperature.
[0105] (3) Preparation of precursor: Dissolve 0.5 mmol Ni(NO3)2▪6H2O, 1 mmol Co(NO3)2▪6H2O, and 8 mmol urea in deionized water and disperse by ultrasonic. Add the prepared solution dropwise to the Te / C dispersion obtained in step (2) under vigorous stirring. Place in an oven at 140 °C for 6 h. After the sample is naturally cooled to room temperature, centrifuge, wash, and dry it to obtain a powdered sample.
[0106] (4) Preparation of tubular NiCo2O4: The powder obtained in step (3) was ground, placed in a porcelain boat, and heated to 500°C at a heating rate of 3°C / min in an air atmosphere, kept at this temperature for 2 h, and the template was removed to obtain a tubular structure spinel oxide high-efficiency oxygen evolution reaction catalyst.
[0107] The tubular spinel oxide prepared in Example 3 is composed of NiCo2O4 ( Figure 1 ).
[0108] Comparative Example 1
[0109] (1) Preparation of Te nanowires: Dissolve 1.2 g polyvinyl pyrrolidone (PVP) and 0.5 mmol Na2TeO3 in 44 mL deionized water and stir. Add 2 mL hydrazine hydrate and 4 mL concentrated ammonia (mass fraction 26 wt%) to the solution. Transfer the final solution to a 100 mL polytetrafluoroethylene hydrothermal reactor and place it in an oven at 180 °C for 3 h. After the sample is cooled to room temperature naturally, add acetone to precipitate the product, centrifuge, and collect the product;
[0110] (2) Preparation of Te / C template: 5 mL of Te nanowires prepared in step (1) were dispersed in 35 mL of glucose solution, stirred, and then transferred to a 100 mL polytetrafluoroethylene hydrothermal reactor and placed in an oven at 180 °C for 8 h. The sample was allowed to cool naturally to room temperature.
[0111] (3) Preparation of precursor: Dissolve 0.5 mmolC4H6O4Zn▪2H2O, 1 mmol Co(NO3)2▪6H2O, and 8 mmol urea in deionized water and disperse by ultrasonic. Add the prepared solution dropwise to the Te / C dispersion obtained in step (2) under vigorous stirring. Place in an oven at 140 °C for 6 h. After the sample is naturally cooled to room temperature, centrifuge, wash, and dry it to obtain a powdered sample.
[0112] (4) Preparation of tubular ZnCo2O4: The powder obtained in step (3) was ground, placed in a porcelain boat, and heated to 350°C at a heating rate of 3°C / min in an air atmosphere, kept at this temperature for 3 h, and the template was removed to obtain a tubular ZnCo2O4 catalyst.
[0113] Weigh 5 mg of the catalyst powder to be tested into a sample tube, add 970 μL of anhydrous ethanol as a solvent and 30 μL of Nafion solution as a binder, mix them and ultrasonically homogenize them to obtain a black catalyst slurry. Transfer 50 μL of the slurry and drip it on a carbon paper with an area of 0.5 cm×0.5 cm several times to ensure that the slurry is evenly coated on the surface of the carbon paper. Dry it at room temperature overnight and set aside. The carbon paper has been treated with ethanol and acetone in advance. The catalyst loading is 1 mg / cm 2 The carbon paper was used as the working electrode, the carbon rod was used as the counter electrode, and the Ag / AgCl electrode was used as the reference electrode to assemble a three-electrode test system. The OER electrochemical performance test was carried out on an electrochemical workstation (CHI 760E). The OER performance test results of the prepared tubular ZnCo2O4 are shown in Figure 2. Figure 5 As shown, at a current density of 10 mA / cm 2 The overpotential at 423 mV is higher than that of tubular NiCo2O4 (10 mA / cm 2 The overpotential at is 327 mV).
[0114] Comparative Example 2
[0115] (1) Preparation of Te nanowires: Dissolve 1.2 g polyvinyl pyrrolidone (PVP) and 0.5 mmol Na2TeO3 in 44 mL deionized water and stir. Add 2 mL hydrazine hydrate and 4 mL concentrated ammonia (mass fraction 26 wt%) to the solution. Transfer the final solution to a 100 mL polytetrafluoroethylene hydrothermal reactor and place it in an oven at 180 °C for 3 h. After the sample is cooled to room temperature naturally, add acetone to precipitate the product, centrifuge, and collect the product;
[0116] (2) Preparation of Te / C template: 5 mL of Te nanowires prepared in step (1) were dispersed in 35 mL of glucose solution, stirred, and then transferred to a 100 mL polytetrafluoroethylene hydrothermal reactor and placed in an oven at 180 °C for 8 h. The sample was allowed to cool naturally to room temperature.
[0117] (3) Preparation of precursor: Dissolve 0.5 mmol Co(NO3)2▪6H2O, 1 mmol Fe(NO3)3▪9H2O, and 8 mmol urea in deionized water and disperse by ultrasonic. Add the prepared solution dropwise to the Te / C dispersion obtained in step (2) under vigorous stirring. Place in an oven at 140 °C for 6 h. After the sample is naturally cooled to room temperature, centrifuge, wash, and dry it to obtain a powdered sample.
[0118] (4) Preparation of tubular CoFe2O4: The powder obtained in step (3) was ground, placed in a porcelain boat, and heated to 350°C at a heating rate of 3°C / min in an air atmosphere, kept at this temperature for 3 h, and the template was removed to obtain a tubular CoFe2O4 catalyst.
[0119] Weigh 5 mg of the catalyst powder to be tested into a sample tube, add 970 μL of anhydrous ethanol as a solvent and 30 μL of Nafion solution as a binder, mix them and ultrasonically homogenize them to obtain a black catalyst slurry. Transfer 50 μL of the slurry and drip it on a carbon paper with an area of 0.5 cm×0.5 cm several times to ensure that the slurry is evenly coated on the surface of the carbon paper. Dry it at room temperature overnight and set it aside. The carbon paper has been treated with ethanol and acetone in advance. The catalyst loading is 1 mg / cm 2 The carbon paper was used as the working electrode, the carbon rod was used as the counter electrode, and the Ag / AgCl electrode was used as the reference electrode to assemble a three-electrode test system. The OER electrochemical performance test was carried out on an electrochemical workstation (CHI760E). The OER performance test results of the prepared tubular CoFe2O4 are shown in Figure 2. Figure 5 As shown, at a current density of 10 mA / cm 2 The overpotential at 10 mA / cm2 is 382 mV, which is better than the OER catalytic performance of tubular NiCo2O4 (10 mA / cm 2 The overpotential at is 327 mV).
[0120] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A spinel oxide catalyst, characterized in that Its active components include NiCo2O4; The structure of the spinel oxide catalyst is a hollow nanotube structure.
2. The spinel oxide catalyst according to claim 1, characterized in that The diameter of the hollow nanotube is 90-120 nm.
3. A method for preparing a spinel oxide catalyst as claimed in claim 1 or 2, characterized in that: The following steps are involved: S1: mixing a soluble nickel salt, a soluble cobalt salt, a precipitant and a solvent to obtain a mixed solution; S2: mixing and reacting the mixed solution with the template dispersion to obtain a precursor, and calcining to obtain a spinel oxide catalyst; The template in the template dispersion is a nanowire with carbon coated on the surface.
4. The preparation method according to claim 3, characterized in that: The soluble cobalt salt includes but is not limited to cobalt nitrate, cobalt sulfate or cobalt chloride; The soluble nickel salt includes but is not limited to nickel nitrate, nickel sulfate or nickel chloride; The precipitating agent includes but is not limited to urea; The solvent includes, but is not limited to, water.
5. The preparation method according to claim 3 or 4, characterized in that: The ratio of the soluble cobalt salt, the soluble nickel salt, the precipitant and the solvent is 1 mmol:0.5 mmol:(7-8) mmol:(5-15) mL.
6. The preparation method according to any one of claims 3 to 5, characterized in that The nanowires are selected from tellurium nanowires.
7. The preparation method according to any one of claims 3 to 6, characterized in that The mixing in step S2 is performed under stirring conditions; the stirring rate is 10000-14000 r / min; The reaction temperature in step S2 is 130-150°C and the reaction time is 6-8 h; The heating rate of the calcination is 2-5°C / min, the calcination temperature is 350-500°C, and the calcination time is 1-3 h.
8. The preparation method according to any one of claims 3 to 7, characterized in that After the precursor is obtained in step S2, it is washed and dried, and then calcined.
9. The preparation method according to claim 8, characterized in that: The washing is performed by washing with ethanol and water for 3 to 5 times respectively; The drying temperature is 60-70° C. and the drying time is 12-18 h.
10. Use of the spinel oxide catalyst according to claim 1 or 2 or the spinel oxide catalyst prepared by the preparation method according to any one of claims 3 to 9 in oxygen evolution by electrolysis of water.
Citation Information
Patent Citations
Nickel cobalt oxide / carbon nanotube composite catalyst, preparation and application thereof
CN105289617A
Metal molybdate / carbon composite nanofiber, preparation method thereof, composite material and application thereof
CN106964362A
One-dimensional porous nanotube and preparation method and application thereof
CN108732230A
Spinel type efficient oxygen evolution electrocatalyst and preparation method thereof
CN111420663A
Bifunctional oxygen electrocatalyst taking hollow carbon nanotube as carrier, preparation and application
CN112886029A
Cited By
Nickel-cobalt-based spinel oxide nano material as well as preparation method and application thereof
CN121065733A